ENHANCEMENT OF QUALITY OF SERVICE IN WIRELESS SENSOR NETWORKS THROUGH ENERGY EFFICIENT QUERY SCHEDULING SCHEME (International Journal of Engineering and Computer Science, 2014)
A Wireless Sensor Network (WSN) consists of sensor nodes capable of collecting information from the environment, process the collected information and direct it to the desired destination (sink). Due to the recent advances in wireless communications, it is important to address the quality of service (Qos) issues. Energy consumption, delay and throughput are some of the Qos issues. The WSN with Static Sink (SS) which uses multihop communication between sensors and SS have certain drawbacks which degrade the Qos of the system. Due to the use of multihop paradigm, the sensors around SS deplete their energy very fast due to high forwarding data traffic. Thus the higher energy consumption by these sensor nodes cannot be avoided. Also, workload of sensor nodes is very high due to the SS. Thus the energy efficient query scheduling scheme is proposed which uses mobile sink to save sensor energy spent for multihop communication. This aims at extending the network lifetime by optimizing the energy consumption, throughput and delay thereby improving the Qos of the system